Variation of microbial load and biochemical activity of ready-to-eat salads in Cyprus as affected by vegetable type, season, and producer - Xylia, Panayiota; Botsaris, George; Chrysargyris, Antonios; Skandamis, Panagiotis; Tzortzakis, Nikos G. (My University, 2019)
Fresh vegetables are important components of an everyday balanced diet making ready to-eat-salads (RTE) a commodity widely consumed. However, in the past few years these products have been linked with outbreaks of salmonellosis and listeriosis; thus the continuous investigation of their safety is an essential requirement. A total of 216 samples of ready-to-eat salads from the Cypriot market were analysed to determine the microbiological quality and safety, along with physicochemical attributes of the salads and identify possible correlations between them. The samples were randomly collected from four retail outlets and correspond to five different salad producing companies. Furthermore, the effects of season, salad producer and type of salad and/or their interactions with the tested parameters were investigated. The results revealed that the higher microbial load among seasons was observed in samples collected during spring. Escherichia coli was found in 11.57% of samples and 2.62% of isolates were found to be able to produce extended spectrum β-lactamase (ESBL). All samples were found negative for Salmonella enterica, whereas Listeria monocytogenes was present in 3.70% of samples. Higher levels of spoilage bacteria (lactic acid bacteria and Pseudomonas spp.) were detected during winter and spring. Additionally, the %CO2 production was affected by the type of salad, while the interaction between producer and type of salad, affected total phenolic content and antioxidant activity of samples. A positive correlation of phenols and antioxidants with the presence of Staphylococcus spp., Pseudomonas spp., E. coli and Bacillus cereus was observed, suggesting that excessive handling increases microbial load and plant stress.
Keywords: Antioxidants; Food safety; Foodborne pathogens; Phenolic content; RTE salads